Antibacterial Behavior of Pyridinecarboxylatesilver(I) Complexes - Paez-Collio, M; Paez-Collio, M; Gulppi-Cabra, M; Gulppi-Cabra, M; Azocar-Guzman, M; Azocar-Guzman, M (2012)
FT-IR spectroscopy of carboxylic groups and viability tests were useful to understand the antibacterial properties of six highly efficient silver(I) pyridinecarboxylate (nicotinic, picolinic and isonicotinic acids) and bipiridinecarboxylate (pyridine-2,3-dicarboxylic, pyridine-2,4-dicarboxylic and pyridine-2,5-dicarboxylic acids) complexes with Ag - O and Ag - N bonds against E. coli (ATCC 25922) and Streptococcus agalactiae (ISP 329-09). The results show a tendency between the nature of Ag - X (X=oxygen and nitrogen) bonds and the rate or efficiency of antibacterial behavior. Copyright © 2012 SIOC, CAS, Shanghai & WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.